A parametric study of a humidification dehumidification (HDH) desalination system using low grade heat sources. (15th November 2015) - He, W.F.; Han, D.; Yue, C.; Pu, W.H.
Highlights: The HDH desalination system coupling with the waste heat plate LGHC is proposed. Performance of the desalination system and the plate LGHC is presented. Influence from the operation pressure on the system performance is investigated. Gained investment ratio is proposed to characterize the desalination system consumption. Abstract: Humidification dehumidification (HDH) desalination system is applicable to recover the low grade heat source to heat the seawater before the humidifier. In the paper, plate heat exchangers are integrated to recover the waste heat from the exhaust in the water heated closed air open water (CAOW) HDH desalination system. The performance of the HDH desalination system as well as the plate type of low grade heat collector (LGHC) is investigated at different operation pressures. Gain investment ratio (GIR) is proposed and defined to depict the overall consumption of the whole system. The simulation results show that the modified heat capacity ratio of the dehumidifier (HCRd) is vital for the performance of the HDH desalination system as well as the plate LGHC with a top value of gain output ratio (GOR) at the balance point, HCRd = 1, and the maximum GOR, GOR = 2.44, results from the raised pressure of p  = 0.15 MPa. Furthermore, taking the cost for the heat transfer surface area of the LGHC and the air and seawater pipes into consideration, it is revealed that the conditions, HCRd > 1, are more economical due to the increase of GIR, which indicates the profit of unit consumption is more significant.